Experimental murine acute lung injury induces increase of pulmonary TIE2-expressing macrophages - Heidi Ehrentraut; Christina Weisheit; Marcel Scheck; Stilla Frede; Tobias Hilbert (BMC, 2018)
Abstract Background Breakdown of the alveolo-capillary wall is pathognomonic for Acute Lung Injury (ALI). Angiopoietins, vascular-specific growth factors, are linked to endothelial barrier dysfunction, and elevated Angiopoietin-2 (ANG2) levels are associated with poor outcome of ALI patients. Specialized immune cells, referred to as 'TIE2-expressing monocytes and macrophages' (TEM), were shown to specifically respond to ANG2 binding. However, their involvement in acute inflammatory processes is so far completely undescribed. Thus, our aim was to assess the dynamics of TEMs in a murine model of ALI. Results Intratracheal instillation of LPS induced a robust pulmonary pro-inflammatory response with endothelial barrier dysfunction and significantly enhanced ANG2 expression. The percentage number of TEMs, assessed by FACS analysis, was more than trebled compared to controls, with TEM count in lungs reaching more than 40% of all macrophages. Such distinct dynamic was absent in all other analyzed compartments (alveolar space, spleen, blood). Incubation of the monocytic cell line THP-1 with LPS or TNF-α resulted in a dose-dependent, significant upregulation of TIE2, suggesting that not recruitment from extra-pulmonary compartments but TIE2 upregulation in resident macrophages accounts for increased lung TEM frequencies. Conclusions For the first time, our data provide evidence that the activity of TEMs changes at sites of acute inflammation.